Elevated Baseline Serum Fibrinogen: Effect on 2‐Year Major Adverse Cardiovascular Events Following Percutaneous Coronary Intervention. Issue 11 (18th November 2017) - Ang, Lawrence; Behnamfar, Omid; Palakodeti, Samhita; Lin, Felice; Pourdjabbar, Ali; Patel, Mitul P.; Reeves, Ryan R.; Mahmud, Ehtisham
Abstract : Background: Elevated fibrinogen is associated with short‐term major adverse cardiovascular events (MACE) after percutaneous coronary intervention, but the relation with late MACE is unknown. Methods and Results: Baseline demographics and 2‐year MACE were recorded among subjects undergoing nonemergent percutaneous coronary intervention. A total of 332 subjects (66.6±19.5 years, 69.9% male, 25.3% acute coronary syndrome) were enrolled. Two‐year MACE (periprocedural myocardial infarction 9.0%, rehospitalization 6.3%, revascularization 12.7%, non–periprocedural myocardial infarction 4.5%, stent thrombosis 0.9%, stroke 1.8%, and death 0.6%) were associated with higher fibrinogen (352.8±123.4 mg/dL versus 301.6±110.8 mg/dL; P <0.001), longer total stent length (40.1±25.3 mm versus 32.1±19.3 mm; P =0.004), acute coronary syndrome indication (38.7% versus 17.8%; P <0.001), number of bare‐metal stents (0.5±1.1 versus 0.2±0.5; P =0.002), and stent diameter ≤2.5 mm (55.8% versus 38.4%, P =0.003). No relation between platelet reactivity and 2‐year MACE was observed. Fibrinogen ≥280 mg/dL (odds ratio [OR] 3.0, confidence interval [CI], 1.6–5.4, P <0.001), total stent length ≥32 mm (OR 2.2, CI, 1.3–3.8, P <0.001), acute coronary syndrome indication (OR 4.1, CI, 2.3–7.5, P <0.001), any bare‐metal stents (OR 3.2, CI, 1.6–6.1, P <0.001), and stent diameter ≤2.5 mm (OR 2.0, CI, 1.2–3.5, P =0.010) were independently associated with 2‐year MACE. Following a landmark analysis excluding periprocedural myocardial infarction, fibrinogen ≥280 mg/dL remained strongly associated with 2‐year MACE (37.0% versus 17.4%, log‐rank P <0.001). Conclusions: Elevated baseline fibrinogen level is associated with 2‐year MACE after percutaneous coronary intervention. Acute coronary syndrome indication for percutaneous coronary intervention, total stent length implanted, and use of bare‐metal stents or smaller‐diameter stents are also independently associated with 2‐year MACE, while measures of on‐thienopyridine platelet reactivity are not.